An improved germline genome assembly for the sea lamprey Petromyzon marinus illuminates the evolution of germline-specific chromosomes - Nataliya Timoshevskaya; Kaan İ. Eşkut; Vladimir A. Timoshevskiy; Sofia M.C. Robb; Carson Holt; Jon E. Hess; Hugo J. Parker; Cindy F. Baker; Allison K. Miller; Cody Saraceno; Mark Yandell; Robb Krumlauf; et al. (Cell Reports, 2023)
Summary: Programmed DNA loss is a gene silencing mechanism that is employed by several vertebrate and nonvertebrate lineages, including all living jawless vertebrates and songbirds. Reconstructing the evolution of somatically eliminated (germline-specific) sequences in these species has proven challenging due to a high content of repeats and gene duplications in eliminated sequences and a corresponding lack of highly accurate and contiguous assemblies for these regions. Here, we present an improved assembly of the sea lamprey (Petromyzon marinus) genome that was generated using recently standardized methods that increase the contiguity and accuracy of vertebrate genome assemblies. This assembly resolves highly contiguous, somatically retained chromosomes and at least one germline-specific chromosome, permitting new analyses that reconstruct the timing, mode, and repercussions of recruitment of genes to the germline-specific fraction. These analyses reveal major roles of interchromosomal segmental duplication, intrachromosomal duplication, and positive selection for germline functions in the long-term evolution of germline-specific chromosomes.